Pillar fragment with Sculptures on its four sides - Temples of India Project Team (Jio Institute, 2024)
A pillar fragment with sculpture on its four sides, of which only two have survived. One image is of a seated Ganesha with four hands and another is a seated figure male figure. The finial of the pillar fragment is shaped like a phamasana (pyramidical type) of shikhara (superstructure or spire). The spire has gavaksha (dormer window) motifs on the sides.